2022
DOI: 10.18203/2394-6040.ijcmph20221332
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on parent mediated intervention programmes for children with autism spectrum disorders in Indi

Abstract: The relevance of identifying effective interventions and rehabilitation of children with autism spectrum disorders (ASD) increases day by day due to the growth, especially in India. One strategy which has been found to be effective to meet the requirements of children and adolescents with ASD is parent-mediated programmes. However, since most studies of this kind have been undertaken in high-income nations, the present research will explore the effect of parent-mediated intervention programmes in India, a coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…One review 14 on PMI in India found the number of papers (13 based on their inclusion criteria) on PMI to be limited in India. Of the papers included in the review, most (61%) of them focused children below 6 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…One review 14 on PMI in India found the number of papers (13 based on their inclusion criteria) on PMI to be limited in India. Of the papers included in the review, most (61%) of them focused children below 6 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…While most interventions have been developed in high-income countries [with only 5% having been developed in Africa, South America, or India ( 7 )], there remains a limited but growing understanding of the transportability of western-developed interventions for use in LMICs ( 8 ). A recent systematic review of 13 studies concluded that caregiver-mediated interventions for children with ASD hold promise in India, the second-most populous country in the world ( 9 ). The systematic review uses a broad interpretation of the term “caregiver-mediated”, to include a range of models, from parent psychoeducation to intensive centre-based models that combine therapist and caregiver-mediated components, with varying levels of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Sengupta et al, ( 6 ) astutely highlighted some ambiguity in the use of the term “caregiver-mediated” within the Indian context, contributing to challenges in interpreting the research evidence in this field [although this is by no means a uniquely Indian challenge; e.g., see ( 10 )]. Of the 13 studies reviewed by Kalorath et al ( 9 ), eight focus on children under 6 years of age (the others include children up to age 9 or 10). Of these, only three report on models that are exclusively caregiver-mediated and relatively resource-efficient ( 6 , 11 , 12 ); others describe programs that involve a therapist-delivered component ( 13 ), are longer in duration and/or more intensive [i.e., ( 14 ): 19-month model ( 15 ), and ( 16 ): daily intervention for 3 months], or programs that focus on behaviour reduction ( 17 ) or parent psychoeducation ( 18 ) rather than direct caregiver coaching to promote the child's developmental progress.…”
Section: Introductionmentioning
confidence: 99%